2012
DOI: 10.1111/j.1600-0412.2012.01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal heart rate patterns in the first and second stages of labor

Abstract: Objective. To analyze typical maternal heart rate (MHR) patterns in the first and second stages of labor. Design. Observational study. Setting. Tertiary care community hospital. Population. Normal term parturients with epidural anesthesia. Methods. Confirmed MHR and uterine activity were simultaneously recorded. The average MHR was analyzed 10 seconds before, as well as at the peak of, each contraction and/or pushing effort. Each woman contributed one datapoint at each time point to the analysis. Main outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Clinicians should be aware of the characteristic features of MHR that differentiate it from FHR to avoid erroneous false reassurance. A recent study has suggested that tracings with repetitive accelerations during contractions (especially when Δ >20 bpm) should be considered MHR until proven otherwise (11).…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should be aware of the characteristic features of MHR that differentiate it from FHR to avoid erroneous false reassurance. A recent study has suggested that tracings with repetitive accelerations during contractions (especially when Δ >20 bpm) should be considered MHR until proven otherwise (11).…”
Section: Discussionmentioning
confidence: 99%
“…1). To ensure the proper selection of L-C segments accompanied by uterine contractions, we also identified unequivocal increments of the displayed maternal heart rate because during well-established frequent contractions the haemodynamic adjustments should generally involve a compensation of cardiac output by an increased heat rate [4,5,17]. L-C and L-NC segments were only selected if these segments involve none or few maternal gross movements.…”
Section: Subjects and Data Collectionmentioning
confidence: 99%
“…In this regard, previous studies have mainly focused on changes of the mean maternal heart rate in relation to uterine contractions [2,4,5]. Recently, Suzuki et al assessed maternal HRV during labour using a power spectral analysis to describe beat-to-beat changes associated with the particular presence of uterine contractions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We welcome the article on maternal heart rate (MHR) analysis during labor by van Veen et al (1). Hopefully, this will bring more visibility to the important issue of misidentification of MHR during fetal heart rate (FHR) recording in labor and to new developments in computerized analysis that are underway (2,3).…”
mentioning
confidence: 99%